2008
DOI: 10.1002/path.2347
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of SerpinA1 and SerpinA3 in HLA‐positive cervical carcinoma

Abstract: In cervical cancer, an important mechanism by which tumour cells escape immune surveillance is loss of HLA class I, enabling tumours to evade recognition and lysis by cytotoxic T lymphocytes. Some tumours, however, escape from immune surveillance without accumulating defects in antigen presentation. We hypothesized that tumours with no or partial loss of HLA class I develop alternative mechanisms to prevent immune elimination. To investigate this hypothesis, genome-wide expression profiling using Illumina arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 31 publications
1
30
1
Order By: Relevance
“…Recently, SerpinA1 and SerpinA3 have been shown to be overexpressed in tumors of a subpopulation of cervical cancer patients. In this study overexpression of these proteins correlated with a poorer survival [64]. Since SerpinA1 and SerpinA3 both have been implicated in inhibition of apoptosis [65,66], overexpression of these proteins may render the tumor cells insensitive for immune mediated apoptosis.…”
Section: Direct Evasion Of the Anti-tumor Responsementioning
confidence: 61%
“…Recently, SerpinA1 and SerpinA3 have been shown to be overexpressed in tumors of a subpopulation of cervical cancer patients. In this study overexpression of these proteins correlated with a poorer survival [64]. Since SerpinA1 and SerpinA3 both have been implicated in inhibition of apoptosis [65,66], overexpression of these proteins may render the tumor cells insensitive for immune mediated apoptosis.…”
Section: Direct Evasion Of the Anti-tumor Responsementioning
confidence: 61%
“…Previously, we have performed a cDNA microarray analysis on 32 tumor specimens. 32 All the cervical cancer samples examined in that study expressed versican (data not shown). In the present study, we have investigated the versican isoforms expressed in 20 tumor samples.…”
Section: The V0 Isoform Is Preferentially Expressed In Cervical Cancermentioning
confidence: 80%
“…33 Furthermore, expression of SerpinA3 has been documented in lung adenocarcinoma 34 and in tandem with SerpinA1 in human leukocyte antigen-positive cervical carcinoma. 35 In this study, in an effort to discover novel biomarkers for the progression of cutaneous SCC, we analyzed expression of the entire serpin family in skin SCC cells using an oligonucleotide-based microarray technique. These results showed that SerpinA1 is markedly overexpressed in primary and metastatic cutaneous SCC cell lines compared with NHEKs.…”
Section: Discussionmentioning
confidence: 99%